2014
DOI: 10.1186/ar4466
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein receptor–related protein 5 governs Wnt-mediated osteoarthritic cartilage destruction

Abstract: IntroductionWnt ligands bind to low-density lipoprotein receptor–related protein (LRP) 5 or 6, triggering a cascade of downstream events that include β-catenin signaling. Here we explored the roles of LRP5 in interleukin 1β (IL-1β)- or Wnt-mediated osteoarthritic (OA) cartilage destruction in mice.MethodsThe expression levels of LRP5, type II collagen, and catabolic factors were determined in mouse articular chondrocytes, human OA cartilage, and mouse experimental OA cartilage. Experimental OA in wild-type, Lr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Both LRP1 and LRP5 involved in OA chondrocyte physiopathology 28,29 . LRP5 can govern Wnt-mediated osteoarthritic cartilage destruction, whereas LRP1-mediated endocytosis is capable of regulating extracellular activity of ADAMTS-5 in articular cartilage 28,29 . Epigenetic alterations of apolipoproteins may also involve in the cartilage destruction of KBD.…”
Section: Discussionmentioning
confidence: 99%
“…Both LRP1 and LRP5 involved in OA chondrocyte physiopathology 28,29 . LRP5 can govern Wnt-mediated osteoarthritic cartilage destruction, whereas LRP1-mediated endocytosis is capable of regulating extracellular activity of ADAMTS-5 in articular cartilage 28,29 . Epigenetic alterations of apolipoproteins may also involve in the cartilage destruction of KBD.…”
Section: Discussionmentioning
confidence: 99%
“…The synovial fluid T cells from the patients with RA were resistant to FasL-induced apoptosis [ 29 ]. Furthermore, accumulated evidence suggested that the Wnt signaling pathway plays an important role in FLS activation, bone resorption, and joint destruction in RA pathogenesis [ 30 - 34 ]. In the context of Wnt signaling in T-cell activation, it has been reported that activation of Wnt signaling in CD4 + CD25 + regulatory T (Treg) cells increased the survival of Treg cells and induced an anergic phenotype in CD4 + CD25 − effector T cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings implied that β-catenin was upregulated in articular cartilage tissue derived from patients with OA (34). Moreover, protein secreted Frizzledrelated protein (Sfrp)3, a secreted negative regulatory factor of Wnt signaling, and mutations of the Frizzledrelated protein (FrzB) gene can increase susceptibility to OA (35).…”
Section: Effect Of Tgf-β In Articular Chondrocyte Degeneration In Oamentioning
confidence: 99%